Let f be a function from the non-negative integers to the positive integers with f ( 0 ) = f ( 1 ) = 1 and f ( y ) f ( x ) f ( y + 1 ) + f ( x − y − 1 ) f ( x ) f ( x − y ) = f ( x + 1 ) . Find the exponent of 3 in the prime factorization of f ( 2 0 1 6 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Suppose x > 0 and let y = x − 1 to get f ( x − 1 ) f ( x ) 2 + f ( x ) = f ( x + 1 ) . I claim that f ( x ) = x ! . To prove this, we use strong induction on x . The base case is trivial, not assume the claim is true for x = k . We have f ( k + 1 ) = f ( k − 1 ) f ( k ) 2 + f ( k ) = k ⋅ k ! + k ! = ( k + 1 ) ! and we are done. So, it suffices to find the exponent of 3 in the prime factorization of 2 0 1 6 ! , which is just ⌊ 3 2 0 1 6 ⌋ + ⌊ 3 2 2 0 1 6 ⌋ + ⌊ 3 3 2 0 1 6 ⌋ + ⌊ 3 4 2 0 1 6 ⌋ + ⌊ 3 5 2 0 1 6 ⌋ + ⌊ 3 6 2 0 1 6 ⌋ = 1 0 0 4
Problem Loading...
Note Loading...
Set Loading...
Substitute x → n + 1 , y → n to get f ( n ) f ( n + 1 ) 2 + f ( n + 1 ) = f ( n + 2 ) f ( n ) f ( n + 1 ) + 1 = f ( n + 1 ) f ( n + 2 ) Define another sequence g ( n ) = f ( n − 1 ) f ( n ) , g ( 1 ) = 1 g ( n + 2 ) = g ( n + 1 ) + 1 , g ( 1 ) = 1 ⇒ g ( n ) = n f ( n ) = n f ( n − 1 ) ⇒ f ( n ) = n ! Hence Index of 3 = 6 7 2 + 2 2 4 + 7 4 + 2 4 + 8 + 2 = 1 0 0 4